Lymphogranuloma venereum diagnoses among men who have sex with men in the UK: interpreting a cross-sectional study using an epidemic phase-specific framework. Issue 7 (12th July 2013) - Hughes, Gwenda; Alexander, Sarah; Simms, Ian; Conti, Stefano; Ward, Helen; Powers, Cassandra; Ison, Catherine; ,
Abstract : Objectives: To investigate the drivers behind the epidemic expansion of lymphogranuloma venereum (LGV) cases in late 2009 to help inform infection control. Methods: An epidemic curve of all LGV diagnoses between 2003 and mid-2012 was plotted and divided into the initial detection period, and endemic, growth and hyperendemic phases. Detailed clinical and behavioural data were collected and logistic regression was used to compare the characteristics of diagnoses made during the growth and endemic phases. Results: Between April 2003 and June 2012, 2138 cases of LGV were diagnosed. Enhanced surveillance data were available for 1370 of whom 1353 were men who have sex with men (MSM). 98% of MSM presented with proctitis, 82% were HIV positive, 20% were hepatitis C virus (HCV) antibody positive, and 67% lived in London. Growth phase cases (n=488) were more likely to report meeting sexual contacts at sex parties (11% vs 6%, p=0.014), unprotected receptive or insertive oral intercourse (93% vs 86%, p=0.001; 92% vs 85%, p=0.001) and sharing sex toys (8% vs 4%; p=0.011), and to be diagnosed HIV positive (86% vs 80%; p=0.014), than endemic phase cases (n=423). Unprotected receptive anal intercourse was equally likely to be reported in both phases (71% vs 73%). After adjustment, cases in the growth phase were more likely to meet new contacts at sex parties (p=0.031) and be HIV positive (p=0.045). Conclusions: Rapid epidemic growth coincided with an intensification of unprotected sexual activity among a core population of HIV-positive MSM. Efforts to develop innovative interventions for this hard-to-reach population are needed.